High density lipoprotein cholesterol levels are an independent predictor of the progression of chronic kidney disease - Baragetti, A.; Norata, Giuseppe; Sarcina, C.; Rastelli, F.; Grigore, L.; Garlaschelli, K.; Uboldi, P.; Baragetti, I.; Pozzi, C.; Catapano, A. (2013)
Objectives: Patients with chronic kidney disease (CKD) often present with reduced plasma HDL cholesterol (HDL-C) levels. Whether this reduction in an epiphenomenon or is involved in disease progression is unclear. The aim of this study was to investigate the relation between HDL-C levels/function and CKD progression in patients with different degrees of disease. Design: A total of 176 patients with CKD [glomerular filtration rate (GFR) 50.3 ± 29.1 mL min -1 ] were recruited and followed for up to 84 months. Lipid profile, metabolic status and kidney function were evaluated at predetermined times. Age-matched control subjects were selected from the PLIC study (n = 453). Scavenger receptor class B member 1 (SR-BI) and ATP-binding cassette transporter A1 (ABCA-1)-dependent efflux of cholesterol were measured in CKD patients and in age-matched control subjects. Results: Low HDL-C levels, diabetes and hypertension were associated with reduced GFR. At follow-up, low HDL-C levels were associated with earlier entry in dialysis or doubling of the plasma creatinine level (P = 0.017); HDL-C levels were the only lipid parameter that affected the progression of CKD (hazard ratio 0.951, 95% confidence interval 0.917-0.986, P = 0.007), independently of the presence of diabetes. Only SR-BI-mediated serum cholesterol efflux was significantly reduced in the group of CKD patients with low HDL-C levels compared to the control group. Conclusions: CKD patients with low levels of plasma HDL-C have a poor prognosis. HDL functionality is also impaired in renal dysfunction. These data support the relevance of HDL in influencing CKD progression. © 2013 The Association for the Publication of the Journal of Internal Medicine.